Anesthesia for bariatric surgery in a patient with Prader-Willi syndrome: Case report - Rada-Ortega, Camilo; Gómez-Ramírez, Carlos Fernando (Colombian Journal of Anesthesiology, 2016)
<p style="color: #000000; font-family: Verdana; font-size: 97%; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Prader-Willi syndrome is a genetic disorder characterized by hypotonia, obesity, short stature, mental retardation, hyperphagia, hypogonadism and low life expectancy. <p style="color: #000000; font-family: Verdana; font-size: 97%; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">We describe the case of a 31-year-old female patient with Prader-Willi syndrome scheduled forbariatric surgery. Anesthetic considerations are reviewed highlighting perioperative complications associated with this syndrome.